De pedras fez terra : um caso de empreendedorismo e investimento no Nordeste Transmontano (Clemente Meneres) - Alves, Jorge Fernandes (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article illustrates a case of entrepreneurialism centred on the Northeast of Trásos-Montes, in Mirandela and neighbouring villages, developed by an ex-emigrant from Brazil, Clemente Meneres, from circa 1870. After several business experiences in Porto, Meneres concentrated his action on the acquisition of land for the production of cork, olive oil and wine, recovering areas which were abandoned, and later organising, in 1902, the Clemente Meneres Society, Ltd., which became a regional model of agricultural exploitation and has remained as a family owned property, keeping its activity until the present day.